Trans-catheter Treatment of Lutembacher Syndrome -A Case Report - Salam, ABM Abdus; Islam, SK Ziarat; Hasan, Kazi Abul; Azad, Saiful Islam; Haque, Ataul; Shariar, Abdullah; Zakia, Naznin Umme; Mita, Shahina Akter (Cardiovascular Journal, 2015)
Lutembacher syndrome is a rare combination of congenital Atrial Septal Defect (ASD) and acquired Rheumatic Mitral Stenosis (MS).It is usually treated by surgical repair with potential risk of cardiopulmonary bypass. With the advancement of interventional methods of treatment it is amenable to nonsurgical transcatheter management. We are reporting a case of Lutembacher syndrome that was successfully treated with percutaneouos Inoue balloon mitral valvuloplasty and device closure of atrial septal defect. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22267 Cardiovasc. j. 2015; 7(2): 162-165